THE CONCEPT OF CONSTITUTIONAL POLITICAL EDUCATION ISLAMIC PERSPECTIVE - Syafrudin, Amang; Saefudin, Didin; Mujahidin, Endin; Ibdalsyah, Ibdalsyah (Riviera Publishing, 2023)
The idealism of the nation and state is often reduced by political behavior that does not reflect maturity and statesmanship. Both by politicians and officials as well as by the community and the people. This can be seen in people's lives when approaching general elections that consider there is no problem with the practice of Money Politics. This study aims to determine the concept of constitutional political education from an Islamic perspective, its implementation in Formal, Informal and Non-formal Education that applies the Tadabbur Methodology and Thematic Interpretation of Constitutional Political Education from an Islamic Perspective. The results of the research that the author finds are the concept of political education, constitutional education in an Islamic perspective associated with Bloom's theory, that education can be felt and produced cognitively, affectively and psychomotorly. If political education can be realized in this picture, the success of political education can affect the world of education, both formal, informal and non-formal. In conclusion, the idealism of nation and state is often threatened by political behavior that does not reflect maturity and statesmanship, both on the part of politicians and officials as well as the community and the people.